Hubungan Potensi Diri dan Motivasi terhadap Minat Melanjutkan Studi Keperguruan Tinggi pada Siswa Kelas XI dan XII di SMKS Semen Padang - Yanna, Rendhi Fitra; Wulansari, Rizky Ema; Mulianti, Mulianti; Primawati, Primawati (TSAQOFAH, 2026)
Students’ interest in continuing their studies to higher education is an important aspect of educational planning, particularly at the vocational secondary school level, which is oriented toward work readiness and career development. This study aims to determine the relationship between self-potential and motivation and interest in continuing studies to higher education among Grade XI and XII students of SMKS Semen Padang in the 2025/2026 academic year. This study employed a descriptive quantitative approach with a correlational method. The research population consisted of 141 students, while a sample of 59 students was determined using the proportionate stratified random sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. The results show that there is a very strong and significant relationship between self-potential and motivation, with a correlation coefficient of 0.913 and a significance value of 0.000 < 0.05. Self-potential also has a very strong and significant relationship with interest in continuing studies to higher education, with a correlation coefficient of 0.893 and a significance value of 0.000 < 0.05. In addition, motivation has a very strong and significant relationship with interest in continuing studies to higher education, with a correlation coefficient of 0.812 and a significance value of 0.000 < 0.05. Simultaneously, self-potential and motivation have a very strong and significant relationship with interest in continuing studies to higher education, with a multiple correlation coefficient (R) of 0.894 and a coefficient of determination (R²) of 0.798. These findings indicate that 79.8% of interest in continuing studies can be explained by self-potential and motivation, while the remaining 20.2% is influenced by other factors outside this study. The conclusion of the study emphasizes that self-potential and motivation are internal factors that strongly contribute to students’ interest in continuing their studies to higher education. The implications of this study emphasize the important roles of schools, teachers, and families in developing students’ self-potential and increasing their motivation so that further education planning can be more optimal.